Kedisiplinan Belajar Siswa Kelas V SD Negeri Pondok Bahar 05 Kota Tangerang - Amilanadzma Hidayah; Mawardi Mawardi; Asep Suhendar (AS-SABIQUN, 2022)
The purpose of this research is to find out how the student learning discipline is and how to improve the fifth grade student learning discipline at Pondok Bahar 05 Public Elementary School, Tangerang City. This study uses a qualitative descriptive method, namely, the researcher analyzes and describes the learning discipline of the students of SD Negeri Pondok Bahar 05 Tangerang City as it is in the condition of a natural object. Data collection techniques through observation, interviews and documentation using data analysis techniques, namely: data reduction (data reduction), data presentation (data display), and draw conclusions/verification (Conclusion/ Verification). The results of this study indicate that student learning discipline in the discipline of study time, discipline in doing assignments, discipline in dressing neatness, discipline in class cleanliness and discipline in the process of learning activities in class is good. There are several factors that cause student discipline in Class 5 SD Negeri Pondok Bahar 05 Tangerang City, one of which is the teacher who always motivates students in the form of rewards, such as small gifts or praise, which makes students more enthusiastic in learning. The school also gives prizes to students who excel to improve student learning achievements.